Analisis Respons Netizen Terhadap Ujaran Kebencian Dalam Kolom Komentar Instagram Gibran Rakabuming Pada Masa Kontestasi Politik 2024 - Fikril Hakim; Irma Yusriani Simamora (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
This study aims to analyze netizens' responses to hate speech in the comments column of Gibran Rakabuming's Instagram account, Vice President of the Republic of Indonesia for the 2024–2029 period. The study used a content analysis method with a descriptive qualitative approach. Data were obtained from netizens' comments on Gibran's uploads from March to April 2025. The results of the study showed various types of hate speech, such as those motivated by politics, physical, psychological, racism, and age. The dominant forms of speech include insults, provocation, and blasphemy. Netizens' responses were divided into two: supporting and rejecting. Supporting responses appeared in the form of justification or sarcasm, while rejecting responses showed awareness of digital ethics and an invitation to respect each other. This study highlights the polarization of opinion in the digital space as well as the importance of digital literacy, social media ethics, and content moderation regulations to create healthy public communication.